(untitled) (International Current Pharmaceutical Journal, 2013)
As traditional drug delivery poses many disadvantages such as difficulty in consumption, the granules were opted to replace tablet dosage forms available in the market. A 23 full factorial design was employed for the formulation and characterization of the granule dosage form of oxcarbazepine. From regression equations we can assess the impact of each factor on the response further contour plots helped to pre-analyze the desired target factor values, in addition optimization process helped to analyze the values of dependent variables. Thus as of the results achieved a preferred response of flow property and drug release was obtained. In the current study, an attempt has been made to minimize possible number of experiments in the formulation of granule dosage forms. Polyvidone is a hydrophilic binder and primellose is a good disintegrate to obtain higher dissolution rate. A part, microwave assisted drying process plays a major role in achieving desired flow properties of granules. DOI: http://dx.doi.org/10.3329/icpj.v2i7.15153 International Current Pharmaceutical Journal, June 2013, 2(7): 115-118